Control of Crop Diseases / [electronic resource] - Carlile, W. R.; Coules, A. (Cambridge : Cambridge University Press, 2012)
Thoroughly revised and updated to reflect current and emerging practices, this book explores modern methods of disease control in field and glasshouse crops. It outlines the major crop diseases, with a particular emphasis on those features of symptomology and life cycle that are most relevant to the development of control measures. Modern diagnostic techniques are considered, focusing on developments in nucleic acid and immunological based procedures and their use in plant quarantine and certification schemes. The potential impact of these advances in molecular technology on plant breeding and disease resistance is also covered. Fungicides are a central part of disease control in the EU and, as such, a comprehensive account of their use forms an important part of the text, along with strategies to minimise the incidence of fungicide resistance in pathogen populations. Looking to the future, the book also addresses legislative, environmental and food safety concerns.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Fungicides